2010
DOI: 10.3197/096327110x531570
|View full text |Cite
|
Sign up to set email alerts
|

Greening our Future and Environmental Values: An Investigation of Perception, Attitudes and Awareness of Environmental issues in Zambia

Abstract: The visibility of environmental problems and the increasing awareness of associated consequences have made environmental issues salient in Zambia. The purpose of this study was to investigate correlations between the social and psychological influences affecting college students in Zambia, and the behaviours perceived by them to be appropriately environmentally friendly. The underlying social and psychological factors that would determine individuals' attitudinal responses toward appropriate environmental beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…These findings are also in line with some prior research. Mweemba and Wu (2010) found that environmental knowledge is important in the formation of individual attitudes. Li et al (2013) found a positive relationship between environmental awareness and green perceived value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are also in line with some prior research. Mweemba and Wu (2010) found that environmental knowledge is important in the formation of individual attitudes. Li et al (2013) found a positive relationship between environmental awareness and green perceived value.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are also in line with some prior research. Mweemba and Wu (2010) found that environmental knowledge is important in the formation of individual attitudes. Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…This paper does not have scope to explore these philosophical issues, but has used ideas from social practice theory to examine how values evolve in people's lives. Debates around individuals' values and their origins have concerned psychology and marketing studies for some decades, and have recently started to be recognised as vitally important within the field of environmental values (for example, by Mweemba and Hongjuan [2010] and Butler [2010]). This discussion considers the contribution that approaches based on social practice theory could make to debates on environmental values, by highlighting the study's key findings, then reflecting on its methodological limitations, before offering three tentative suggestions for policy and practice.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Yet, we found only three studies that included both action-focused items (agent-action) and aim-focused items (agent-aim or agent-action-aim) in one scale ( Estrada et al, 2017 ; Q. He et al, 2019 ; Mweemba & Hongjuan, 2010 ).…”
Section: Three Advantages Of the Triple-a Frameworkmentioning
confidence: 99%